Tożsamość dziś: narracyjna? dialogowa? performatywna? - Partyga, Ewa (Wydawnictwo Naukowe UAM, 2008)
Crisis of disembodied and disengaged subject, reduced to Cogito and perceived in terms of substance and essence, contributed to the emergence of multiple, both modern and postmodern, propositions of describing how the Self, rendered now as an uncertain and dispersed entity, is constituted, negotiated or constructed. This article discusses three types of identity concepts popular in contemporary humanities, all of them accentuating the relational character of the self: the narrative or storied Self, the dialogical Self and the performative Self. The discussion focuses on the usefulness of the categories of drama and dialogue as the tools in re-thinking the question of the de-centered Self and its identity.
Identity today: narrative? dialogical? performative?